2021
DOI: 10.1038/s41598-021-02449-y
|View full text |Cite
|
Sign up to set email alerts
|

Two novel human anti-CD25 antibodies with antitumor activity inversely related to their affinity and in vitro activity

Abstract: High tumor regulatory T (Treg) cell infiltration is associated with poor prognosis of many cancers. CD25 is highly expressed on tumor Treg cells and is a potential target for Treg deletion. Previously characterized anti-CD25 antibodies appear to have limited efficacy in tumor inhibition. Here we identified two human anti-CD25 antibodies, BA9 and BT942, which did not prevent the activation of IL-2R signaling pathway by IL-2. BT942 had weaker binding and cytotoxic activity to human CD25-expressing cell lines tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…IL2RA can influence the activity of Treg cells to assist in the regulation of immunological tolerance 69 . Targeting and eliminating Treg cells through the use of CD25 antibodies have been recognized as a key mechanism for tumor inhibition and the elimination of immunosuppression 70 . Overall, our results suggest that lower airway dysbiosis in lung cancer is associated with distinct cytokine profiles and microbial compositions.…”
Section: Discussionmentioning
confidence: 72%
“…IL2RA can influence the activity of Treg cells to assist in the regulation of immunological tolerance 69 . Targeting and eliminating Treg cells through the use of CD25 antibodies have been recognized as a key mechanism for tumor inhibition and the elimination of immunosuppression 70 . Overall, our results suggest that lower airway dysbiosis in lung cancer is associated with distinct cytokine profiles and microbial compositions.…”
Section: Discussionmentioning
confidence: 72%
“…It relieves immune suppression in the TME. BA1106 is expected to compensate for the shortcomings of current anti‐PD‐1 therapies 91 …”
Section: Drugs Targeting Cd25mentioning
confidence: 99%
“…If the follow‐up clinical trial of IL‐2 non‐blocking anti‐CD25 antibodies gains success, it will bring a new type of immunotherapy to patients with increased Tregs frequency in the TME 90‐93 …”
Section: Drugs Targeting Cd25mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that non‐IL‐2‐blocking anti‐CD25 antibodies could preferentially deplete Tregs without suppressing Teff activation, potentially improving tumor immunity. Currently, two non‐IL‐2‐blocking anti‐CD25 antibodies RG6292 and BA1106, developed by Roche and Boan Biotech respectively, have been reported with enhanced tumor immunity 37,38 . These results indicated that the different epitopes on CD25 antigen may exert significant impact on immune regulation function of anti‐CD25 antibodies.…”
Section: Introductionmentioning
confidence: 97%